Gender inequality and job quality in Europe - Peter Mühlau (Management Revue, 2011)
In this paper, I examine whether and to which degree the quality of work and employment differs between men and women and how these gender differences are shaped by societal beliefs about 'gender equality.' Using data from the 2004 wave of the European Social Survey, I compare the jobs of men and women across a variety of measures of perceived job quality in 26 countries. Key findings are that job quality is gendered: Jobs of men are typically characterized by high training requirements, good promotion opportunities and high levels of job complexity, autonomy and participation. Jobs for women, in contrast, are less likely to pose a health or safety risk or to involve work during antisocial hours. However, contrary to expectation, the job profiles of men and women are not more similar in societies with gender egalitarian norms. While women are relatively more likely to be exposed to health and safety risks, work pressure and demands to work outside regular working time, in more gender- egalitarian societies their work is not, relative to men's, more skilled, complex or autonomous. Neither do more egalitarian societies provide more opportunities for participation and advancement for women than less egalitarian societies.
Keywords: A14; J16; J24; 650; job quality; gender inequality; gender egalitarianism